2014
DOI: 10.1139/cjc-2014-0099
|View full text |Cite
|
Sign up to set email alerts
|

High open circuit voltage organic solar cells based upon fullerene free bulk heterojunction active layers

Abstract: We have recently reported on a small organic molecule containing a bithiophene core with end-capping phthalimide units (PthTh 2 Pth) that exhibited a H-aggregation tendency in the solid state and high electron mobility in organic field effect transistors. In this contribution, we have studied both the physical and electrical properties of poly(3-hexylthiophene) (P3HT) and PthTh 2 Pth thin films by measuring the optical absorption, Frontier molecular orbital energy levels, photoluminescence quenching, thermal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…HPI-BT can be synthesized in a two-step protocol and functionalized with low-cost phthalimide end cap units, another building block that has been incorporated in many electron-accepting materials. 79,[109][110][111][112][113] The synthesis of this material exemplies the straightforward and versatile synthesis of many non-PDI acceptors, wherein a single synthetic protocol can be adapted to access several materials. HPI-BT has one of the widest band-gaps of non-fullerene acceptors at 2.3 eV, with a relatively high lying LUMO level that sits at À3.5 eV.…”
Section: Planar Small Moleculesmentioning
confidence: 99%
“…HPI-BT can be synthesized in a two-step protocol and functionalized with low-cost phthalimide end cap units, another building block that has been incorporated in many electron-accepting materials. 79,[109][110][111][112][113] The synthesis of this material exemplies the straightforward and versatile synthesis of many non-PDI acceptors, wherein a single synthetic protocol can be adapted to access several materials. HPI-BT has one of the widest band-gaps of non-fullerene acceptors at 2.3 eV, with a relatively high lying LUMO level that sits at À3.5 eV.…”
Section: Planar Small Moleculesmentioning
confidence: 99%
“…The importance of ideal donor acceptor pairings is clearly illustrated in this work, a good example of this can be seen by comparing the devices made using M4 with each donor, for DTS(FBTTh 2 ) 2 : M4 devices a modest PCE of 0.43% is achieved; however, for the P3HT : M4 devices a PCE that is essentially negligible was observed (Table 2). Overall the PCEs are significantly lower than related devices fabricated with fullerene acceptors 37,39 but based on film morphology studies (see Fig. S31 and S32, ESI †) we believe the PCEs obtained for M1-M7 devices are currently limited by excessive phase separation.…”
Section: Single Crystal X-ray Diffraction Study Of M5mentioning
confidence: 71%
“…36 This phthalimidethiophene based small molecule has also been used in our group to produce OSCs with high V oc , B1.0 V, when paired as an acceptor with P3HT. 37 Moving forward, we incorporated the diketopyrrolopyrrole (DPP) chromophore as a central building bock in this design and demonstrated that DPP and phthalimide can be used together to make low band gap electron transporting materials. 38 In another study we have investigated the use of the isoindigo (IS) chromophore as a central building block and demonstrated that it can also be used to produce low band gap materials, that when used as the electron-accepting component in OSCs, gave devices with a V oc of B1.0 V. 39 We have also performed a theoretical investigation on a series of electron deficient building blocks with acceptor-donor-acceptordonor-acceptor (A 1 DA 2 DA 1 ) architecture (where A 1 and A 2 have different electron affinities).…”
Section: Introductionmentioning
confidence: 99%
“…16 In this work we investigate the side chain engineering of a well-studied D-A p-conjugated molecular framework synthesized in our group, 5,5 0 (2,2 0 -bithiophene-5,5 0 -diyl)bis(2-alkylphthalimide). [17][18][19][20][21][22] In this D-A framework, the bithiophene electron-rich core (D) is flanked with electron-deficient imide terminal units (A). Imide-flanked materials have shown considerable success in organic p-conjugated materials, [23][24][25][26] and are attractive due to their well-studied self-assembly properties, and the ability to functionalize the imido-nitrogen with a wide range of alkyl side chains.…”
Section: Introductionmentioning
confidence: 99%